2010
DOI: 10.1016/j.juro.2010.06.145
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Predictors of Renal Function Decrease After Laparoscopic Radical Nephrectomy

Abstract: Glomerulosclerosis severity in nonneoplastic parenchyma can predict the rate of renal function decrease after radical nephrectomy. This histopathological parameter should be assessed in all tumor nephrectomy specimens, given that preserving renal function is important for quality of life and clinical outcome in patients with renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…1 Recent reports have highlighted the utility and value of diagnosing nonneoplastic renal disease in the tumor-free portion of the nephrectomy or partial nephrectomy specimen. [2][3][4] Studies of radical nephrectomy with long-term follow-up have demonstrated significant decline in renal function in 13% to 36% of patients. 1,5 Clinical parameters associated with postnephrectomy renal insufficiency include female sex, hypertension, diabetes, and preoperative proteinuria in univariate analysis, and preoperative serum creatinine level, hypertension, and preoperative proteinuria in multivariate analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent reports have highlighted the utility and value of diagnosing nonneoplastic renal disease in the tumor-free portion of the nephrectomy or partial nephrectomy specimen. [2][3][4] Studies of radical nephrectomy with long-term follow-up have demonstrated significant decline in renal function in 13% to 36% of patients. 1,5 Clinical parameters associated with postnephrectomy renal insufficiency include female sex, hypertension, diabetes, and preoperative proteinuria in univariate analysis, and preoperative serum creatinine level, hypertension, and preoperative proteinuria in multivariate analysis.…”
mentioning
confidence: 99%
“…Even though one had limited follow-up (6 months) in a small group of patients (39), the authors showed a statistically significant increase in serum creatinine levels of 11 patients with vascular disease and 10 with diabetic nephropathy compared with the 14 without such change. 4 A second study by Gautam et al 2 reported that global glomerulosclerosis (GS) significantly correlated with postoperative renal function decline in 49 patients who underwent radical nephrectomy and were followed for 3 to 60.8 months.…”
mentioning
confidence: 99%
“…To focus on the evaluation of erectile function, the severity of ED was graded as no (26-30), mild (22)(23)(24)(25), mild to moderate (17)(18)(19)(20)(21), moderate (11)(12)(13)(14)(15)(16) or severe (6-10) using the IIEF-erectile function domain data according to a previous study. 11 Five (7.7%), ten (15.4%), eleven (16.9%), nine (13.8%) and thirty (46.2%) patients were categorized as no, mild, mild to moderate, moderate and severe ED, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, a few studies have demonstrated the utility of global GS in the histopathological evaluation of nephrectomized normal kidney parenchyma as a predictive marker for progression of renal functional impairment after RN. 19,20 Our study is the first attempt to evaluate whether global GS is a useful biomarker for the prediction of ED. Because low levels of global GS extent and post-RN percent eGFR decrease were associated with no/mild ED in the univariate analysis, normal renal function preservation may be a minimum requirement for normal erectile function.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the presence and extent of glomerolosclerosis in normal parenchyma has been shown to be commensurate with deterioration in postoperative renal function, although this trend was not noted for features such as arteriosclerosis or interstitial fibrosis/ tubular atrophy. (Gautam et al, 2010;McCann et al, 2009) …”
Section: Preoperative Risk Stratification Schematamentioning
confidence: 99%